Totální endoprotéza kyčelního kloubu za použití AMIS přístupu: operační technika, vhodnost přístupu u obézních pacientů, hodnocení souboru - Palásek, P; Mašát, P; Řeháček, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: This manuscript aims to introduce our surgical technique, with an emphasis on the latest recommendations. The AMIS technique is discussed in more detail in patients with Class II and Class III obesity. We seek to prove the premise claiming that the anteversion and inclination values observed in this group of patients do not differ signifi cantly from those observed in patients with the recommended BMI index. We will also compare the risk of neurovascular bundle injury and postoperative complication rate regarding the surgical wound. MATERIAL AND METHODS: Patients who underwent surgery using the AMIS method in the period between 1/2020 and 4/2023 were assessed retrospectively. The study included 1150 implantations. The entire study population was assessed for neurovascular bundle injury and surgical wound healing complications. For this purpose, the patients were divided into two groups based on the BMI, namely BMI < 35 kg/m2 (n=1042) and BMI > 35 kg/m2 (n=108). In patients with the BMI ≤ 25 kg/m2 (n=280) and BMI ≥ 35 kg/m2 (n=108), the inclination and anteversion values were compared. Standard centered AP view X-rays of their operated joints were assessed. The Liaw's method was used to calculate the anteversion and inclination. RESULTS: In group one of patients with BMI ≤ 25 kg/m2 (208 women and 72 men), the arithmetic mean of acetabular anteversion was 25.4° (median 25°) and inclination was 38.3° (median 38°). In group two, which consisted of patients with BMI ≥ 35 kg/m2 (59 women and 49 men), the total arithmetic mean of acetabular anteversion was 25.1° (median 25) and inclination was 37.6° (median 37.5°). The anteversion and inclination were assessed using the Mann-Whitney test for equality of medians. The value of 0.05 was chosen as the level of signifi cance. The resulting p-value was 0.5359 in anteversion and 0.3763 in inclination. Since the p-value of both anteversion and inclination was greater than the chosen level of signifi cance, their medians have not been confi rmed to differ signifi cantly. A total of 6 cases of femoral nerve injury was reported, i.e. 0.5% out of 1150. Therefore, the risk of injury was 0.4% in the group with BMI < 35 kg/m2 (n=1042). On the contrary, in the group of patients with BMI > 35 kg/m2 (n=108), the risk was 2%. No injury to femoral artery was reported. The surgical wound healing complications were seen in a total of 87 cases (7.6%). In the group with BMI < 35 kg/m2 , healing complications of the surgical wound were observed in 7.4% of cases, with the need for revision surgery in 7 patients. In the group with BMI > 35 kg/ m2 , healing complications occurred in 13% of patients and wound revision was necessary in 4 cases. DISCUSSION: Our results are consistent with those in the published studies that also show no signifi cant difference in anteversion and inclination of components in the compared groups of obese patients. We also agree with the other authors that the rate of complications regarding surgical wound healing is higher in these patients. The risk of neurovascular bundle injury in this study population is not higher than the standard. CONCLUSIONS: The results obtained in our study population show that this method can also be used in patients with higher BMI, with no concern about the implantation of components in malposition or a higher risk of neurovascular injury. Nonetheless, potentially higher risk of surgical wound healing should be considered when this approach is opted for. With the appropriate surgical technique, AMIS is a safe method and, in our view, the fi rst choice especially for obese patients. KEY WORDS: AMIS, anteversion, inclination, hip joint, obesity, BMI, implantation, total joint replacement.
Keywords: Retrospective Studies; obezita; retrospektivní studie; náhrada kyčelního kloubu; Male; Arthroplasty, Replacement, Hip; Surgical Wound; mužské pohlaví; chirurgická rána; Hip Joint; Humans; lidé; Obesity; ženské pohlaví; Female; kyčelní kloub